Esaform 2021 2021
DOI: 10.25518/esaform21.2056
|View full text |Cite
|
Sign up to set email alerts
|

Material Modelling of Fabric Deformation in Forming Simulation of Fiber-Metal Laminates – A Review on Modelling Fabric Coupling Mechanisms

Abstract: During forming of complex fiber-metal laminates (FML), compressive stress zones occur. In pure textile forming, these compressive stresses typically lead to extensive wrinkling. In FML forming, however, wrinkling is partly hindered by the metal layers. Thus, combined stress states occur, where compression influences the deformation. In forming simulation, these compressive stresses can lead to erroneous formation of shear bands within the fabric layer, if the deformation behavior is not modelled correctly. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Since experimental studies have shown interdependencies between distinct strain components, hyperelastic models with invariant-coupling, e.g., biaxial-tension [18] and tension-shear coupling [19], have been proposed. A recent review on modelling coupling mechanisms in woven fabrics, with particular focus on invariant-based constitutive modeling is given in [20].…”
Section: Introductionmentioning
confidence: 99%
“…Since experimental studies have shown interdependencies between distinct strain components, hyperelastic models with invariant-coupling, e.g., biaxial-tension [18] and tension-shear coupling [19], have been proposed. A recent review on modelling coupling mechanisms in woven fabrics, with particular focus on invariant-based constitutive modeling is given in [20].…”
Section: Introductionmentioning
confidence: 99%
“…Based on this theory, many researchers [2,15,23,26], have developed hyperelastic constitutive models to investigate the mechanical behaviour of dry fabrics under large deformations. Indeed, the non-linear macroscopic material behavior has to be set in the constitutive equations [17]. It is also worth noting that in the framework of in-plane shear tests, two major methods have been proposed and studied i.e Picture Frame Test and Bias Extension Test.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanical property would normally lead to the formation of wrinkles as discussed in [16]. Werner et al [17], in their review on the modeling of fabric coupling mechanisms commented on the shear stress characteristic during angular variation of the rovings. Immediately the yarns come into contact with each other, the shear force increases, which is definitely attributed to the lateral compaction of rovings.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations